Circadian variation in expression of G1 phase cyclins D1 and E and cyclin-dependent kinase inhibitors p16 and p21 in human bowel mucosa. - Griniatsos, John; Michail, Othon P; Theocharis, Stamatios; Arvelakis, Antonios; Papaconstantinou, Ioannis; Felekouras, Evangelos; Pikoulis, Emmanouel; Karavokyros, Ioannis; Bakoyiannis, Chris; Marinos, George; Bramis, John; Michail, Panayiotis O (World J Gastroenterol, 2006)
AIM: To evaluate whether the cellular proliferation rate in the large bowel epithelial cells is characterized by circadian rhythm. METHODS: Between January 2003 and December 2004, twenty patients who were diagnosed as suffering from primary, resectable, non-metastatic adenocarcinoma of the lower rectum, infiltrating the sphincter mechanism, underwent abdominoperineal resection, total mesorectal excision and permanent left iliac colostomy. In formalin-fixed and paraffin-embedded biopsy specimens obtained from the colostomy mucosa every six hours (00:00, 06:00, 12:00, 18:00 and 24:00), we studied the expression of G(1) phase cyclins (D(1) and E) as well as the expression of the G(1) phase cyclin-dependent kinase (CDK) inhibitors p16 and p21 as indicators of cell cycle progression in colonic epithelial cells using immunohistochemical methods. RESULTS: The expression of both cyclins showed a similar circadian fashion obtaining their lowest and highest values at 00:00 and 18:00, respectively (P<0.001). A circadian rhythm in the expression of CDK inhibitor proteins p16 and p21 was also observed, with the lowest levels obtained at 12:00 and 18:00 (P<0.001), respectively. When the complexes cyclins D(1) -p21 and E-p21 were examined, the expression of the cyclins was adversely correlated to the p21 expression throughout the day. When the complexes the cyclins D(1) -p16 and E-p16 were examined, high levels of p16 expression were correlated to low levels of cyclin expression at 00:00, 06:00 and 24:00. Meanwhile, the highest expression levels of both cyclins were correlated to high levels of p16 expression at 18:00. CONCLUSION: Colonic epithelial cells seem to enter the G(1) phase of the cell cycle during afternoon (between 12:00 and 18:00) with the highest rates obtained at 18:00. From a clinical point of view, the present results suggest that G(1) -phase specific anticancer therapies in afternoon might maximize their anti-tumor effect while minimizing toxicity.
Keywords: Aged; circadian rhythm; Colon; Cyclin D1; Cyclin E; Cyclin-Dependent Kinase Inhibitor p16; Cyclin-Dependent Kinase Inhibitor p21; Female; G1 Phase; Humans; Immunohistochemistry; Intestinal Mucosa; Male; Middle Aged